2017
DOI: 10.1104/pp.17.00085
|View full text |Cite
|
Sign up to set email alerts
|

A Key Role for Apoplastic H2O2 in Norway Spruce Phenolic Metabolism

Abstract: Apoplastic events such as monolignol oxidation and lignin polymerization are difficult to study in intact trees. To investigate the role of apoplastic hydrogen peroxide (H 2 O 2 ) in gymnosperm phenolic metabolism, an extracellular lignin-forming cell culture of Norway spruce (Picea abies) was used as a research model. Scavenging of apoplastic H 2 O 2 by potassium iodide repressed lignin formation, in line with peroxidases activating monolignols for lignin polymerization. Time-course analyses coupled to candid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
48
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 137 publications
(196 reference statements)
2
48
0
Order By: Relevance
“…4; Supplemental Table S3). Eleven of the pathway genes detected in this study have been reported previously as induced twofold or greater under extracellular lignin-forming conditions in a cell culture of Norway spruce (Laitinen et al, 2017).…”
Section: Gene Expression In Developing Tracheids and Ray Cellssupporting
confidence: 55%
See 4 more Smart Citations
“…4; Supplemental Table S3). Eleven of the pathway genes detected in this study have been reported previously as induced twofold or greater under extracellular lignin-forming conditions in a cell culture of Norway spruce (Laitinen et al, 2017).…”
Section: Gene Expression In Developing Tracheids and Ray Cellssupporting
confidence: 55%
“…Bar 5 50 mm. 20.8) in the lignin-forming cell culture of spruce during lignin formation (Laitinen et al, 2017). Six PEROXI-DASEs, on the other hand, were more highly expressed in ray cells than in tracheids (P adj , 0.05; Supplemental Table S4).…”
Section: Many Genes Encoding Oxidative Enzymes Are Highly Expressed Imentioning
confidence: 99%
See 3 more Smart Citations